Aspectos fisiológicos de gramíneas nativas do bioma Pampa em relação ao excesso de alumínio - Machado, Liliane Corrêa (2020)
The Pampa Biome is one of the main biomes in Brazil. Natural pastures cover more than 500 species belonging to the Poaceas family, with grasses being the species with the highest proportion and occurrence in this area, representing about 65 to 85% of the forage mass in natural pastures. Trivalent aluminum (Al+³) is the main limiting factor for the production of several agricultural crops and its toxicity causes, in large part, physiological disturbances and imbalance in the absorption of water and nutrients, resulting in less plant growth. In view of the variability and versatility of grasses in the Pampa Biome and their development and adaptability in environments considered to be not very fertile, it is necessary to study and understand the physiological responses of four species of native grasses exposed to excess Al+³, as well as to evaluate which species are more adapted to this condition. The objective of the study was to evaluate the physiological aspects of four species of grasses native to the Pampa Biome in relation to the excess of Al³+. Study I was conducted in a cultivation system using sand as a substrate, the treatments being composed of three concentrations of Al³+ (0, 75 and 150 mg Al³+ L-¹) and four species of grasses (Paspalum urvillei, Axonopus affinis, Paspalum plicatulum and Andropogon lateralis), irrigated with nutrient solution. After 40 days of cultivation, gas exchange, concentration of photosynthetic pigments, dry mass of aerial parts and roots, concentration of Al³+ and nutrients in tissues were determined. Study II was conducted in an aerated hydroponic cultivation system, using the same treatments of Al³+ and species of study I. At 15 days of cultivation, in exposure to Al³+,the leaf gas exchange was evaluated, followed by the collection of plants for determination of Al³+ concentration and nutrients in plant tissues, root biometry, dry mass production, photosynthetic pigments concentrations and total soluble proteins, guaiacol peroxidase (POD) activity, hydrogen peroxide (H2O2) concentrations and lipid peroxidation (TBARS). In study I, the excess of Al³+ in the substrate increased the concentration of the metal both in the roots and in the aerial part of the four grass species, a fact correlated to the reduction in the total dry mass production of A. affinis, P. plicatulum and A. lateralis On the other hand, P. urvillei, despite accumulating Al³+ in the roots, did not show any change in dry matter production. The gas exchange in the leaves, in general, was compromised mainly in the presence of 150 mg Al³+ L-¹. P. plicatulum showed the greatest change in the photosynthetic pigments concentration by Al³+. The positive correlations between the concentrations of Ca and Mg in the aerial part can show the importance of these nutrients as attenuating agents of the toxic effects promoted by Al³+. P. urvillei, among the species evaluated, proved to be tolerant to the excess of Al³+, while A. affinis, P. plicatulum and A. lateralis were more sensitive to Al³+. In study II the increments of Al³+ (75 and 150 mg L-¹) increased the concentration of Al³+ mainly in the roots of the P. urvillei and A. affinis, presenting themselves as more tolerant to the excess of Al³+, due to the greater presence of the metal in the root system. On the other hand, P. plicatulum and A. lateralis were characterized as more sensitive to Al³+ toxicity. Al³+ negatively affected the morphology of the root system, as well as the production of dry mass of the four species. In addition to promoting them, the reduction of net CO2 assimilation. P. urvillei there was no change in photosynthetic pigments. POD activity was compromised by the toxic effect of Al³+, which mainly promoted the increase in H2O2 in the shoot, consequently causing an increase in lipid peroxidation, resulting in the low response of the antioxidant system of grass species. The nutrient concentrations were altered with the increase of Al³+ (75 and 150 mg L-¹), with Ca, Mg and K being the most affected, obtaining inverse correlations to Al³+ concentrations.